Historical Echoes in Mythical Realms: Unveiling New Perspectives in the Mahabharatha Epic (International Journal of Food and Nutritional Sciences, 2022)
“Time creates all things and time destroys them all. Time burns all creatures and timeagain extinguishes that fire” (Anukramanika Parva, Adi Parva). The pluralism of Hinduism sets itapart from other modern religious practices. While other religions are diverse, Hinduism ispolylithic, or the polar opposite of monolithic, as Wendy Doniger points out. Wendy DonigerO’Flaherty is an American Indologist with a five-decade professional career. ‘The texts wrestlewith competing truths, rather than offer pat answers” (Hindus, 43-44). The Mahabharata is theworld’s longest epic poetry, and it has been called the world’s longest poetry. It has approximately1,00,000 shlokas, over 2,00,000 individual poem lines (each shloka is a couplet), and extendedprose passages in its fullest version. The Mahabharata is nearly 10 times the length of the Iliad(762 BC) and Odyssey (8th century BCE) combined or around four times the length of the Odyssey.The Mahabharata has been studied extensively for its layers, which have been identified anddated. Some of the current Mahabharata’s elements can be traced back to Vedic times.